Pembuatan Indeks Beranotasi Jurnal Teknik Sipil Koleksi Perpustakaan Politeknik Negeri Padang - Syafitri, Dilla; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2018)
AbstractÂ Making An Annotated Index of Civil Engineering Library Collection Journal Padang State Polytechnic. Journal Library and Archival Information Study Program. Indonesian and Regional Languages and Literature Department. Faculty of Social and Arts. Padang State University. In this paper discussed about making an annotated index of civil engineering journals from the Padang Polytechnic library. The purpose of this study was to describe the indexing process with annotations in management thesis at the Padang State Polytechnic library. The method used is descriptive method which is explained as it is. Data was collected by direct observation and filing interviews with librarians at the Padang State Polytechnic Library. The process of making an annotated index is (1) initial observations of Civil Engineering Journals conducted directly at the Padang State Polytechnic Library, after observations the journal collection consists of 7 journals, and 160 articles; 2) Selection of Civil Engineering Journals at the Padang Polytechnic Library, after collection and selection, the journal collection consists of 7 journals, copies and 60 articles; (3) making a journal description is done by recording annotated index data. The information recorded is the name of the journal, volume, month and year of publication of the journal, article title, author's name, and article page number; (4) article annotation, aims to provide a description of the contents to the user. Making annotations is done by first reading the entire article, understanding the purpose of the article; (5) determining keywords that aim to simplify and accelerate information retrieval. Keywords are taken from the article title, article abstract, and article content; (6) indexing of journal articles with several provisions such as index of author names, index of titles and index of keywords arranged in alphabetical order; (7) Typing an annotated index.Keywords: annotated index; civil engineering journal